2015
DOI: 10.1007/s00484-015-1021-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical attributes and heat stress in dairy cattle from different genetic groups

Abstract: Dairy cattle raised under harsh conditions have to adapt and prevent heat stress. The aim of this study was to evaluate physical characteristics and their association with heat tolerance in different genetic groups of dairy cattle. Thickness of the skin and coat, length and number of hairs, body measurements, as well as physiological parameters and body temperatures by infrared thermography were determined in 19 Holstein and 19 Girolando (½ and ¾ Holstein) cows. The Holstein cattle were less tolerant to heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…HOXC13 gene has been found to determine skin thickness (Wu et al 2009(Wu et al , 2013. Skin thickness and number of hair follicles are reported to have an effect on thermoregulation; thermotolerant cattle have thicker skin than heat susceptible cattle breeds (Alfonzo et al 2016). In general, indicus cattle have thicker skin than taurus cattle (Pan 1963;Alfonzo et al 2016).…”
Section: Hair Coat Type and Colormentioning
confidence: 99%
“…HOXC13 gene has been found to determine skin thickness (Wu et al 2009(Wu et al , 2013. Skin thickness and number of hair follicles are reported to have an effect on thermoregulation; thermotolerant cattle have thicker skin than heat susceptible cattle breeds (Alfonzo et al 2016). In general, indicus cattle have thicker skin than taurus cattle (Pan 1963;Alfonzo et al 2016).…”
Section: Hair Coat Type and Colormentioning
confidence: 99%
“…In domestic cattle, mitogenome analysis provides information regarding how functional traits like body size and tolerance are evolved in different lineages over temporal and spatial scales (Achilli et al, 2009(Achilli et al, , 2008 ). Thus, by simultaneously measuring both physiological and molecular responses, it is possible to assess differential tolerance among K E Y W O R D S adaptive tolerance, heat stress, livestock, phenotypic plasticity, phylogeny, size dependence dissimilar genetic groups of animals (Albon et al, 2017;Alfonzo et al, 2016;Mitchell et al, 2018). Additionally, mitogenome analysis can map out the observed differential adaptive trait variations at physiological and molecular levels to the phylogeny of different genetic groups (Lajbner, Pnini, Camus, Miller, & Dowling, 2018).…”
mentioning
confidence: 99%
“…Previous studies indicated that the density of hair follicles in Bos indicus is higher than that of Bos taurus (Turner & Schleger ), and the number of hair follicles is reported to have an effect on thermoregulation (Alfonzo et al ). The denser hair results in greater protection from radiant heat gain (Jian et al ), which is why the whole body of DHH cattle is covered with hairs that are extremely short, dense and closely applied to the skin (Yunnan Commission of Animal Genetic Resources ) (Fig.…”
Section: The Candidate Genes Are Associated With Heat Tolerance and Imentioning
confidence: 99%